2009
DOI: 10.1002/cne.22199
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the diabetes‐associated gene TCF7L2 in adult mouse brain

Abstract: Polymorphisms of the gene TCF7L2 (transcription factor 7-like 2) are strongly associated with the development and progression of type 2 diabetes. TCF7L2 is important in the development of peripheral organs such as adipocytes, pancreas, and the intestine. However, very little is known about its expression elsewhere. In this study we used in situ hybridization histochemistry to show that TCF7L2 has a unique expression pattern in the mouse brain. TCF7L2 is expressed in two distinct populations. First, it is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 66 publications
2
23
1
2
Order By: Relevance
“…Lee and collaborators reported high TCF7L2 expression in thalamic and tectal adult mouse brain structures, with lower expression level in the hypothalamus and additional areas [66]. Further studies showed that TCF7L2 expression in the CNS is characterized by a variety of splice variants.…”
Section: Discussionmentioning
confidence: 98%
“…Lee and collaborators reported high TCF7L2 expression in thalamic and tectal adult mouse brain structures, with lower expression level in the hypothalamus and additional areas [66]. Further studies showed that TCF7L2 expression in the CNS is characterized by a variety of splice variants.…”
Section: Discussionmentioning
confidence: 98%
“…These studies, however, have re-directed our attention to the expression and function of Tcf7l2 and Wnt signaling in pancreatic islets, especially in the pancreatic b cells. Tcf7l2 is abundantly expressed in the mouse intestinal epithelia and adipocytes (Barker et al 1999, Ross et al 2000, and in the central nervous system (Lee et al 2009). Inconsistent findings about Tcf7l2 expression in the mouse pancreas, however, can be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The antisera used in the present study are all commercially available, have been validated before and used by different laboratories (Scott et al, 2009); (Zhao et al, 2008); (Lee et al, 2009); (Clarkson et al, 2009, Caron et al, 2010). …”
Section: Methodsmentioning
confidence: 99%